2019
DOI: 10.1016/j.scitotenv.2018.12.460
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven QMRA model for selected water supply systems in Norway accounting for raw water sources and treatment processes

Abstract: Formulating effective management intervention measures for water supply systems requires investigation of potential long-term impacts. This study applies an integrated multiple regression, random forest regression, and quantitative microbial risk assessment (QMRA) modelling approach to assess the effect of climate-driven precipitation on pathogen infection risks in three drinking water treatment plants (WTPs) in Norway. Pathogen removal efficacies of treatment steps were calculated using process models. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Therefore, we also perform work to assess how future climate scenarios will challenge raw water quality and the water treatment capacity in a follow up study that is a part of the same research project. Using the data from this study and future climate scenarios combined with modelling of treatment effect and QMRA [ 31 ] to assess probability of disease is needed to address and prepare for a changing climate with more extreme weather events and potential need for increased treatment capacity. This will be central to minimize the risk and burden of waterborne disease in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we also perform work to assess how future climate scenarios will challenge raw water quality and the water treatment capacity in a follow up study that is a part of the same research project. Using the data from this study and future climate scenarios combined with modelling of treatment effect and QMRA [ 31 ] to assess probability of disease is needed to address and prepare for a changing climate with more extreme weather events and potential need for increased treatment capacity. This will be central to minimize the risk and burden of waterborne disease in the future.…”
Section: Discussionmentioning
confidence: 99%
“…was determined using bacteria and virus data measured by Haramoto et al (2006), Katayama et al (2008), La Rosa et al (2010), and Silverman et al (2013), and is similar to the range of raw wastewater R NoV:FIB determined in the present study. Similarly, Eregno et al (2016) and Mohammed & Seidu (2019) assumed a conversion factor of 10 À1.06 NoV per E. coli in QMRA of surface waters used for recreational purposes and drinking water, respectively, based on norovirus concentrations measured in nearby wastewater effluent.…”
Section: Influence Of R Nov:fib On Qmra-estimated Risksmentioning
confidence: 99%
“…A learning algorithm that is widely used in predictive modelling, even when the number of variables exceeds the sample size greatly, is the random forest (RF) algorithm (Tyralis and Papacharalampous, 2017). It has already been applied successfully in various microbiological studies to solve classification problems (Baudron et al, 2013;Peters et al, 2007), for nowcasting (Vincenzi et al, 2011) and forecasting (Mohammed and Seidu, 2019;Parkhurst et al, 2005). The studies revealed the potential of RF for microbial predictive modelling and this explains the choice of the learning algorithm for the current study.…”
Section: Introductionmentioning
confidence: 97%